Braillestick: desenvolvimento e avaliação do dispositivo de entrada para pessoas com deficiência visual baseado na máquina de escrever em Braille - Santana, Kayo Costa de (2021)
The Braille system enables the literacy and autonomy of several visually impaired people around the world. One of the most efficient technologies for Braille writing is the Braille machine, however, even with such an important social function, its use is restricted to few people and few environments (e.g. schools, universities, specialized centers), due to the high cost of its acquisition. In this context, we propose the development and evaluation of Braillestick, an input device for computers, with a writing procedure similar to that of the Braille machine, contributing to the inclusion of people with visual impairments, through the offer of low cost assistive technology. For this, we developed a qualitative and quantitative research, using the case study as the method of investigation, through which it was possible to evaluate Braillestick. For this evaluation, we collected data regarding usability and user experience, as well as the speed and error rate of users, through the serious game “The Braille Typist”, enabling the comparison of Braillestick with the keyboard (mapped for Braille writing). The results obtained, through experiments carried out with 10 volunteers, point out no statistically significant differences between Braillestick and keyboard, considering the speed and the error rate of the users, thus showing that the users can benefit equally of both solutions, in relation to these aspects. By comparing the speed averages of Braillestick users with other works found in scientific knowledge bases, it was possible to verify that its speed was higher than 9 of 16 works compared. Finally, Braillestick was also well rated by its users in terms of usability and user experience (attractiveness, perspicuity, efficiency, effectiveness, reliability, stimulation and innovation) and the grades given by its users revealed a good evaluation, with grades above 90% in all criteria. With the presented results, we point that Braillestick can be considered as an accessible technology, due to its characteristics of price, size, weight and ease of transport, expanding the possibilities of social and digital inclusion of people with visual impairments.